2018
DOI: 10.1038/s41598-018-31525-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of brain networks supports consciousness and verbal intelligence

Abstract: How are the myriad stimuli arriving at our senses transformed into conscious thought? To address this question, in a series of studies, we asked whether a common mechanism underlies loss of information processing in unconscious states across different conditions, which could shed light on the brain mechanisms of conscious cognition. With a novel approach, we brought together for the first time, data from the same paradigm—a highly engaging auditory-only narrative—in three independent domains: anesthesia-induce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 86 publications
(92 reference statements)
1
39
0
Order By: Relevance
“…Previously, changes in static (Di Perri et al, 2016;Naci et al, 2018;Stamatakis et al, 2010) and dynamic functional connectivity (Barttfeld et al, 2015;Cavanna et al, 2018;Demertzi et al, 2019;Golkowski et al, 2019) in different states of consciousness have been widely reported. We advance .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, changes in static (Di Perri et al, 2016;Naci et al, 2018;Stamatakis et al, 2010) and dynamic functional connectivity (Barttfeld et al, 2015;Cavanna et al, 2018;Demertzi et al, 2019;Golkowski et al, 2019) in different states of consciousness have been widely reported. We advance .…”
Section: Discussionmentioning
confidence: 99%
“…Due to equipment malfunction or impairments with the anaesthetic procedure three participants were excluded (1 male). Thus, 16 participants were included in this study (Naci et al, 2018).…”
Section: Participants -Lon Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding a complex narrative (such as a movie's plot) requires a viewer to remember previous events, pay attention to what is currently happening, make predictions about the future consequences of current events, and integrate this information over time, all of which depends on frontoparietal executive processing (Naci et al, 2014). In previous studies, reduced synchrony in this network has been associated with 'losing the plot' during deep sedation (Naci et al, 2018), and in patients with severe brain damage (Naci et al, 2014). Thus, this decrease in inter-subject correlation in the lateral prefrontal cortex may suggest that participants in the ASD group are also failing to grasp elements of the plot in the way that the other participants do.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that individuals were attending to different features of the movie, which has been shown to influence the degree of neural synchrony (Nguyen et al, 2019), although previous work has confirmed that movies similar to 'Despicable me' maintain the viewers' attention (Hasson, Landesman, et al, 2008;Naci et al, 2015). It is also unlikely that participants were asleep during the movie, as most of the visual network was synchronized across the three groups during the movie, which is not observed when individuals are sedated (Naci et al, 2018).…”
Section: Discussionmentioning
confidence: 99%